Infectious microbial diseases and host defense responses in Sydney rock oysters - Raftos, David A.; Kuchel, Rhiannon; Aladaileh, Saleem; Butt, Daniel (Frontiers in Microbiology, 2014)
Aquaculture has long been seen as a sustainable solution to some of the world’s growing food shortages. However, experience over the past 50 years indicates that infectious diseases caused by viruses, bacteria and eukaryotes limit the productivity of aquaculture. In extreme cases, these types of infectious agents threaten the viability of entire aquaculture industries. This article describes the threats from infectious diseases in aquaculture and then focuses on one example (QX disease in Sydney rock oysters) as a case study. QX appears to be typical of many emerging diseases in aquaculture, particularly because environmental factors seem to play a crucial role in disease outbreaks. Evidence is presented that modulation of a generic subcellular stress response pathway in oysters is responsible for both resistance and susceptibility to infectious microbes. Understanding and being able to manipulate this pathway may be the key to sustainable aquaculture.